Antitumor activity and pharmacologic characterization of the depsipeptide analog as a novel histone deacetylase/ phosphatidylinositol 3‐kinase dual inhibitor. Issue 7 (19th May 2017) - Saijo, Ken; Imai, Hiroo; Chikamatsu, Sonoko; Narita, Koichi; Katoh, Tadashi; Ishioka, Chikashi
Abstract : Histone deacetylase (HDAC)/phosphatidylinositol 3‐kinase (PI3K) dual inhibition is a promising strategy for the treatment of intractable cancers because of the advantages of overcoming potential resistance and showing synergistic effects. Therefore, development of an HDAC/PI3K dual inhibitor is reasonably attractive. Romidepsin (FK228, depsipeptide) is a potent HDAC inhibitor. We previously reported that depsipeptide and its analogs have an additional activity as PI3K inhibitors and are defined as HDAC/PI3K dual inhibitors. Subsequently, we identified FK‐A11 as the most potent analog and reported its biochemical, biological, and structural properties as an HDAC/PI3K dual inhibitor. In this study, we reveal the in vitro and in vivo efficacy of FK‐A11 in HT1080 fibrosarcoma and PC3 prostate cancer cell xenograft mouse models. FK‐A11 showed in vivo antitumor activity by both i.v. and i.p. administration in a dose‐dependent manner. In both xenograft models, FK‐A11 showed superior antitumor effects compared to other depsipeptide analogs in accordance with in vitro anti‐cell proliferation effects and the potency of HDAC/PI3K dual inhibition. In addition, we showed evidence of HDAC/PI3K dual inhibition accompanying antitumor efficacy in xenograft tumor tissues by immunohistochemistry. We also detailed pharmacokinetic characterization of FK‐A11 in mice. These findings will be essential for guiding further preclinical and clinical studies. Abstract : The depsipeptide analog FK‐A11 is an HDAC/PI3K dual inhibitor. FK‐A11 showed anti‐tumor activity in human cancer cell xenograft mouse models, with evidence of HDAC/PI3K dual inhibition in tumor tissues. Furthermore, pharmacokinetic characterization of FK‐A11 in mice was analyzed. These findings will be essential for further preclinical and clinical studies.